2022
DOI: 10.3389/fnut.2022.806115
|View full text |Cite
|
Sign up to set email alerts
|

Bacillus velezensis A2 Inhibited the Cecal Inflammation Induced by Zearalenone by Regulating Intestinal Flora and Short-Chain Fatty Acids

Abstract: Zearalenone (ZEA) as an estrogen-like mycotoxin can cause the inflammatory injury of the cecum. How to reduce the harm that ZEA causes to humans and animals is a current concern for researchers. In this study, we aimed to ascertain whether Bacillus velezensis A2 (A2) could alleviate injury caused by ZEA by regulating the intestinal flora and the content of short chain fatty acids in the cecum among mice. Our results showed that Bacillus velezensis A2 improved the fold height, myometrial thickness, and crypt de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 39 publications
2
5
0
Order By: Relevance
“…The suppression of SCFA producing bacteria was confirmed with the decreased caecal SCFAs concentration in our study. Our finding is consistent with a previous study that revealed a significantly lower caecal SCFAs content in the ZEA-treated animal group [52]. Low abundance of SCFAs, major metabolites from gut microbiota, and SCFAs-producing bacteria are linked to colon cancer development [53].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The suppression of SCFA producing bacteria was confirmed with the decreased caecal SCFAs concentration in our study. Our finding is consistent with a previous study that revealed a significantly lower caecal SCFAs content in the ZEA-treated animal group [52]. Low abundance of SCFAs, major metabolites from gut microbiota, and SCFAs-producing bacteria are linked to colon cancer development [53].…”
Section: Discussionsupporting
confidence: 93%
“…Alteration in the microbial community are known to influence the development of diseases such as irritable bowel disease, obesity, liver disease and cancer [40][41][42]. Consistent with a previous study that revealed a significantly lower cecal SCFAs content in the ZEA-treated animal group [43], we observed reduced cecal SCFAs and SCFA-producing bacteria, Rikenella [44] and Rikenellaceae RC9 gut group, and the anti-inflammatory bacterium Candidatus Saccharimonas [35]. A low abundance of SCFAs, major metabolites from the gut microbiota, and SCFA-producing bacteria has been linked to colon cancer development [45].…”
Section: Discussionsupporting
confidence: 91%
“…The present results showed that the proportions of short-chain fatty acids-producers (SCFAs-producers), lactic acid bacteria (LAB), and digestive enzyme-producing bacteria were much higher in the LPC-supplemented groups. SCFAs-produces Faecalibacterium (especially F. prausnitzii ), an indicator of intestinal health, and Bacillus (especially B. velezensis ), which has been evidenced to be able to ameliorate intestinal inflammation [ 55 , 56 ], had comparatively higher proportion in turbot diets with LPC. Meanwhile, a recent study in turbot showed that the dietary Bacillus species enhanced the abundance of Ralstonia , which was also significantly positively correlated with immune parameters such as AKP and ACP [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…A2 inhibits the expression of inflammatory-related genes such as IL-6, TNF-α, and IL-1 β, alleviating the cellular inflammatory response induced by mycotoxins [ 40 ]. The excessive release of these inflammatory factors is associated with cell damage [ 41 ].…”
Section: Discussionmentioning
confidence: 99%